Strigea falconis Infection in Bute magnirostris in Brazil - Olinda, Roberio Gomes; Alves de Souza, Maxson Cosme; Dias, Glenison Ferreira; Augusto Marietto-Goncalves, Guilherme; Silva, Reinaldo Jose da [UNESP]; Batista, Jael Soares (Univ Fed Rio Grande Do Sul, 2015)
Background: Bute inagnirosiris, popularly known as roadside hawk belongs to the family Accipitridae, Ciconiiformes. The specimen is common throughout Brazil inhabiting open areas, tolerating disturbed areas very well, but avoiding dense forests. The trematodes are common parasites in the intestines of birds of prey, with scant notice of pathogenic infections. However, severe infections of trematodes Strigeidae family have been previously reported as a cause of anemia, diarrhea, enteritis, weight loss and death. This paper aims to report the occurrence of infection in S. Falcon is in B. magnirostris diagnosed by post mortem examination. Case: The specimen of B. magnirostris, male, young was sent for necropsy at the Laboratory of Veterinary Pathology, Federal Rural University of Semi-Arid (UFERSA), Mossorfi-RN, Brazil, With a history of apathy, anorexia, diarrhea and death in one course of 24 It The free bird life and even puppy had been captured for training and practice of falconry shortly before the clinical manifestation of infection (time of captivity uninformed). On physical examination ruffled feathers, cachexia and pallor of skeletal muscle was observed. At necropsy there was severe enteritis with petechiae and accumulation of liquid contents into the duodenum. Fifty-two trematodes were found set in duodenal mucosa. The other organs and structures showed no changes. Fragments of all organs were harvested, fixed in 10% -formalin buffered, routinely processed for histopathology and stained with hematoxylin and eosin (HE). Parasites were carefully collected, washed in saline,.fixed, processed and identified according to the morphology and taxonomy. Histologically, the lesions were restricted to the duodenum and were characterized by melting, severe atrophy and necrosis of the epithelial cells of the intestinal inflammatory infiltrate (consisting of lymphocytes, plasma cells and eosinophils) in the lamina propria, in addition to trematodes infiltrated the mucosa and lamina propria. These were 60-80 mm in diameter, consisted of parenchymal body enclosed by the integument. In some cross sections of the parasite was possible to observe the presence of cectun, testis and uterus, with some variations between sections; there were also yellowish eggs and coated with a delicate membrane. The trematodes contain approximately 1 mm in length and used as morphology and taxonomy has been identified as S. Falconis. Discussion: S. Falconis is a trematode intestinal parasite of birds of prey, with reports of its occurrence in Europe, North America and Central. In neotropical regions is described the occurrence of the subspecies S. Falconis brasillana. Although the absence of clinical signs is a common pattern, parasitism by trematodes may become evident, common to captivity stress conditions, and thus infections, even for low pathogenic parasites can cause diarrhea, anorexia, weight loss and death, as reported in this paper. A factor that possibly contributed to the scant notice is its small size, which makes the observation of this parasite in analysis of necropsy in non-pathological conditions and also not familiar with the technical laboratories in the morphological shape of the eggs, which creates difficulty in finding the parasite in parasitological analysis in captive animals, Despite being considered poorly pathogenic trematodes, epidemiologically, the presence of the parasite should be considered a health risk to free-living predators, newly captive in parks, zoos, veterinary hospitals, triage center for wildlife and creators, as they may express pathogenicity in immunosuppressed animals, This work contributes to recording the presence S. plconis parasitizing the duodenal mucosa of B. magnirostris in Brazil.
Keywords: bird; platyhefininthes; parasitology; pathology avian; animal health